Effects of dietary vitamin B1 on growth performance, blood metabolites, body composition, intestinal enzyme activities and morphometric parameters of juvenile yellow catfish (Pelteobagrus fulvidraco). (7th June 2020) - Zhao, Hongxia; Chen, Bing; Huang, Yanhua; Cao, Junming; Wang, Guoxia; Chen, Xiaoying; Mo, Wenyan
Abstract: The effects of vitamin B1 on growth, blood metabolites, body composition, intestinal enzyme activities and morphometric parameters were evaluated by a 63‐day feeding trial in Pelteobagrus fulvidraco fed diets containing vitamin B1 with 4.29, 6.02, 7.86, 11.94 and 19.05 mg/kg, respectively. Results showed that 7.86 mg/kg vitamin B1 resulted in significantly higher weight gain (WG), specific growth rate (SGR) and protein efficiency ratio (PER) ( p < .05). Serum triglyceride, cholesterol and whole‐body lipid were observed in 11.94 mg/kg vitamin B1 group significantly higher than those in 4.29 mg/kg group, accompanied by the lower serum glucose content in the same group ( p < .05). Significantly higher values of whole‐body protein, serum total protein, relative intestinal length, fold height, intestinal trypsin, amylase, alkaline phosphatase, Na+/K+‐ATPase, γ‐glutamyl transpeptidase, creatine kinase, muscular layer thickness and intestosomatic index were observed in 7.86 mg/kg vitamin B1 group compared with those in 4.29 mg/kg group ( p < .05). These results suggested that diets supplemented with vitamin B1 improved growth performance, feed utilization, intestinal digestive and absorption capacity of juvenile yellow catfish. The optimal dietary vitamin B1 requirements estimated using a two‐slope broken‐line model based on WG and PER of yellow catfish were 7.42 and 6.01 mg/kg, respectively.